Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-02-09T17:23:17+01:00
Sn = 2n² - 6n

Sn - Sn-1 = an

Sn-1 = 2(n - 1)² - 6(n - 1) = 2(n² - 2n + 1) - 6n + 6 = 2n² - 4n + 2 - 6n + 6 = 2n² - 10n + 8

Sn - Sn-1 = = 2n² - 6n - (2n² - 10n + 8) = 2n² - 6n - 2n² + 10n - 8 = 4n - 8
czyli
an = 4n - 8
a₁ = 4*1 - 8 = 4 - 8 = - 4

an = a₁ + (n - 1)*r
an - a₁ = (n - 1)*r /:(n - 1) (oczywiście zakładamy, że n≠1)
r = an - a₁ / n - 1 (podstawiamy wcześniej obliczone an i a₁)
r = 4n - 8 + 4 / n - 1
r = 4n - 4 / n - 1
r = 4(n - 1) / n - 1
r = 4

Odp. Różnica ciągu wynosi 4.